Immune response and blood–brain barrier dysfunction during viral neuroinvasion. Issue 2 (February 2021) - Chen, Zhuangzhuang; Li, Guozhong
The blood-brain barrier (BBB), which protects the CNS from pathogens, is composed of specialized brain microvascular endothelial cells (BMECs) joined by tight junctions and ensheathed by pericytes and astrocyte endfeet. The stability of the BBB structure and function is of great significance for the maintenance of brain homeostasis. When a neurotropic virus invades the CNS via a hematogenous or non-hematogenous route, it may cause structural and functional disorders of the BBB, and also activate the BBB anti-inflammatory or pro-inflammatory innate immune response. This article focuses on the structural and functional changes that occur in the three main components of the BBB (endothelial cells, astrocytes, and pericytes) in response to infection with neurotropic viruses transmitted by hematogenous routes, and also briefly describes the supportive effect of three cells on the BBB under normal physiological conditions. For example, all three types of cells express several PRRs, which can quickly sense the virus and make corresponding immune responses. The pro-inflammatory immune response will exacerbate the destruction of the BBB, while the anti-inflammatory immune response, based on type I IFN, consolidates the stability of the BBB. Exploring the details of the interaction between the host and the pathogen at the BBB during neurotropic virus infection will help to propose new treatments for viral encephalitis. Enhancing the defense function of the BBB, maintaining the integrity of the BBB, and suppressing the pro-inflammatory immune response of the BBB provide more ideas for limiting the neuroinvasion of neurotropic viruses. In the future, these new treatments are expected to cooperate with traditional antiviral methods to improve the therapeutic effect of viral encephalitis.